2022
DOI: 10.1186/s13075-021-02710-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lung function decline on time to hospitalisation events in systemic sclerosis-associated interstitial lung disease (SSc-ILD): a joint model analysis

Abstract: Background Interstitial lung disease (ILD) is a common organ manifestation in systemic sclerosis (SSc) and is the leading cause of death in patients with SSc. A decline in forced vital capacity (FVC) is an indicator of ILD progression and is associated with mortality in patients with SSc-associated ILD (SSc-ILD). However, the relationship between FVC decline and hospitalisation events in patients with SSc-ILD is largely unknown. The objective of this post hoc analysis was to investigate the rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In our analyses, an increase in the rate of decline in FVC % predicted of 1 percentage point over 52 weeks increased the risk of acute exacerbation or death by 12%, and the risk of hospitalization or death by 9%. An analysis of the SENSCIS trial using similar methodology found a similar association between decline in FVC % predicted and risk of hospitalization or death over 52 weeks 38 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our analyses, an increase in the rate of decline in FVC % predicted of 1 percentage point over 52 weeks increased the risk of acute exacerbation or death by 12%, and the risk of hospitalization or death by 9%. An analysis of the SENSCIS trial using similar methodology found a similar association between decline in FVC % predicted and risk of hospitalization or death over 52 weeks 38 …”
Section: Discussionmentioning
confidence: 88%
“…An analysis of the SENSCIS trial using similar methodology found a similar association between decline in FVC % predicted and risk of hospitalization or death over 52 weeks. 38 Strengths of our analyses include the large and heterogeneous population of subjects, the standardized procedure for measuring FVC and the use of a joint modelling approach that allows for estimation of time-dependent effects that considers temporality (i.e., FVC changes precede events at the individual level). Our analyses were limited by the time frame over which FVC decline and mortality were assessed (52 weeks), the use of different definitions for an acute exacerbation across the trials, and the lack of collection of data on acute exacerbations in the SENSCIS trial.…”
Section: Discussionmentioning
confidence: 99%
“…Nintedanib was started on patients with progressive fibrosing ILD as previously defined [ 17 , 30 , 32 ]. PFTs in routine examination and in clinical trials mainly focus on FVC, DLco, and forced expiratory volume in 1 s (FEV1) measurements [ 33 , 34 , 35 ]. The % of the predicted values of the FVC, Dlco, and FEV1 was preferred as it is considered a primary outcome value and provides an adjusted, reliable, and simple prognostic factor [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data from the SENSCIS trial found that a decline in FVC increased hospitalizations and death, and a decrease in FVC of 3% was associated with 43% higher hospitalization and mortality 91 . Thus, although remaining an important complication and cause of death in SSc, lung fibrosis is now better understood and more manageable, with evidence-based treatment including medications to slow progression of fibrosis (nintedanib and possibly pirfenidone) and to potentially prevent ILD changes in early dcSSc (tocilizumab).…”
Section: Management Of Lung Manifestationsmentioning
confidence: 99%